Carbon Monoxide-Releasing Molecule-2 Ameliorates Particulate Matter-Induced Aorta Inflammation via Toll-Like Receptor/NADPH Oxidase/ROS/NF-κB/IL-6 Inhibition. (13th July 2021) - Vo, Thi Thuy Tien; Hsu, Chien-Yi; Wee, Yinshen; Chen, Yuh-Lien; Cheng, Hsin-Chung; Wu, Ching-Zong; Lin, Wei-Ning; Lee, I-Ta
Abstract : Particulate matter (PM), a major air pollutant, may be associated with adverse cardiovascular effects. Reactive oxygen species- (ROS-) dependent proinflammatory cytokine production, such as interleukin-6 (IL-6), is a possible underlying mechanism. Carbon monoxide- (CO-) releasing molecule-2 (CORM-2) which liberates exogenous CO can exert many beneficial effects, particularly anti-inflammation and antioxidant effects. The purpose of this study was to explore the protective effects and underpinning mechanisms of CORM-2 on PM-induced aorta inflammation. Here, human aortic vascular smooth muscle cells (HASMCs) were utilized as in vitro models for the assessment of signaling pathways behind CORM-2 activities against PM-induced inflammatory responses, including Toll-like receptors (TLRs), NADPH oxidase, ROS, nuclear factor-kappa B (NF- κ B), and IL-6. The modulation of monocyte adherence and HASMC migration, that are two critical cellular events of inflammatory process, along with their regulators, including intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and matrix metalloproteinase-2 (MMP-2) and MMP-9, in response to PM by CORM-2, were further evaluated. Finally, mice experiments under different conditions were conducted for the in vivo evaluation of CORM-2 benefits on the expression of inflammatory molecules including IL-6, ICAM-1, VCAM-1, MMP-2, and MMP-9. Our results found that PM could induce aorta inflammation in vitro and in vivo, as evidenced by the increase of IL-6 expression that was regulated by the TLR2 and TLR4/NADPH oxidase/ROS/NF- κ B signaling pathway, thereby promoting ICAM-1- and VCAM-1-dependent monocyte adhesion and MMP-2- and MMP-9-dependent HASMC migration. Importantly, our experimental models demonstrated that CORM-2-liberated CO effectively inhibited the whole identified PM-induced inflammatory cascade in HASMCs and tissues. In conclusion, CORM-2 treatment may elicit multiple beneficial effects on inflammatory responses of aorta due to PM exposure, thereby providing therapeutic value in the context of inflammatory diseases of the cardiovascular system.